2012
DOI: 10.1039/c2cp40285h
|View full text |Cite
|
Sign up to set email alerts
|

Turn-directed folding dynamics of β-hairpin-forming de novo decapeptide Chignolin

Abstract: Realistic mechanistic pictures of β-hairpin formation, offering valuable insights into some of the key early events in protein folding, are accessible through short designed polypeptides as they allow atomic-level scrutiny through simulations. Here, we present a detailed picture of the dynamics and mechanism of β-hairpin formation of Chignolin, a de novo decapeptide, using extensive, unbiased molecular dynamics simulations. The results provide clear evidence for turn-directed broken-zipper folding and reveal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 53 publications
3
38
1
Order By: Relevance
“…From this graph we can see that only the two native-like states have low C α -C α distances for the 1–10 pair. This implies that these residues are the last to come together when folding, and the first to come apart when unfolding, which is in direct conflict with the results of Enemark et al 34 It is possible that the OPLS-AA force field used in their work demonstrates different behavior than the CHARMM22 force field used here. As we move higher up the stem, nodes change from red to blue in a monotonic fashion, indicating a zipper-like mechanism.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…From this graph we can see that only the two native-like states have low C α -C α distances for the 1–10 pair. This implies that these residues are the last to come together when folding, and the first to come apart when unfolding, which is in direct conflict with the results of Enemark et al 34 It is possible that the OPLS-AA force field used in their work demonstrates different behavior than the CHARMM22 force field used here. As we move higher up the stem, nodes change from red to blue in a monotonic fashion, indicating a zipper-like mechanism.…”
Section: Resultscontrasting
confidence: 73%
“…30 It has served as an excellent system for theoretical study 3437 since it is the one of the smallest molecules that exhibits stable secondary structure. The folded structure of the molecule consists of a central turn region (residues 4–7) flanked by three amino acids on each side, which form the stem of the hairpin, which is stabilized by hydrogen bonding interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For chignolin, we have recently shown that formation of the native turn (NT) region (Pro4-Gly7) drives folding and marks the beginning of the downhill zipping stage of the folding cascade19. Other recent studies of different β-hairpins have also reported turn-directed mechanisms, providing support for a general turn-centric folding scenario1315.…”
Section: Resultsmentioning
confidence: 91%
“…For example, given that turns exist at Thr8 and Trp9 only, propagation to turns at Thr6 and Gly7 typically occurs on the order of a few ns, while further propagation to Glu5 and Pro4 occurs about 2 orders of magnitude more slowly. As folding is driven by NT formation19, the timescale of turn propagation to Pro4 thus provides a lower bound for the overall folding time, estimated to be ~1 μs1720.…”
Section: Resultsmentioning
confidence: 99%